2001
DOI: 10.1007/s005350170103
|View full text |Cite
|
Sign up to set email alerts
|

HBV-related fulminant hepatic failure: successful intensive medical therapy in a candidate for liver transplantation

Abstract: Fulminant hepatic failure (FHF) usually has a fatal prognosis without liver transplantation. We describe the case of a woman who developed FHF, and was evaluated as a candidate for liver transplantation, but who was cured without transplantation through intensive medical care that included glucagon-insulin therapy, methylprednisolone pulse therapy, interferon beta and lamivudine administration, cyclosporine administration, and high-volume hemodiafiltration and plasma exchange. In a patient with FHF who is a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…29,30 Acute physiological changes, age, and chronic health evaluation scoring systems have also been used for predicting mortality in hospitalized cirrhotic patients. 31 However, few studies have focused on the relative weighting of various index variables in terms of their contribution to the prediction of death in chronic severe hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Acute physiological changes, age, and chronic health evaluation scoring systems have also been used for predicting mortality in hospitalized cirrhotic patients. 31 However, few studies have focused on the relative weighting of various index variables in terms of their contribution to the prediction of death in chronic severe hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…Acute severe hepatitis often evolves into FHF, and patients with FHF cannot be cured without transplantation. However, organ shortage is a serious problem worldwide, and especially in Japan, where liver transplantation from brain‐dead donors is uncommon 5 . Instead, partial‐liver transplantation from parents or siblings is common.…”
Section: Discussionmentioning
confidence: 99%
“…However, laboratory data may suggest evolution into FHF before immunosuppressive and antiviral therapy are begun, including increased TB and INR, decreased direct bilirubin‐to‐total bilirubin ratio, total cholesterol, cholinesterase, and albumin 1,6 . Intensive medical therapy is dictated by the laboratory data 5,7 …”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that patients with HBV-related fulminant liver failure could be was cured with intensive medical therapy including regeneration therapy, immunosuppressive therapy, antiviral therapy and artificial liver support. 9 This combination therapy is carried out for patients with fulminant hepatitis and late-onset hepatic failure in Japan. 5 Lamivudine was reported to be efficacious for the treatment of acute liver failure.…”
Section: Author's Replymentioning
confidence: 99%
“…During the combination therapy, it is necessary to monitor the HBV-DNA levels and prevent infections and bleeding carefully. 9 The use of the corticosteroids for the treatment of chronic hepatitis B has failed to demonstrate a significant benefit. However, corticosteroid treatment is considered to suppress an excessive immune response.…”
Section: Author's Replymentioning
confidence: 99%